2006
DOI: 10.1002/cncr.22261
|View full text |Cite
|
Sign up to set email alerts
|

Survival of men with clinically localized prostate cancer treated with prostatectomy, brachytherapy, or no definitive treatment

Abstract: BACKGROUND.The optimal treatment for men with early stage prostate cancer remains undefined. Survival of such patients after surgery, brachytherapy, or no definitive therapy was investigated specifically to determine the impact of age at diagnosis.METHODS.In all, 60,290 men diagnosed with organ‐confined, low and moderate grade prostate cancer between 1988 and 2002 were retrospectively identified from centers participating in the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
1
35
0
1
Order By: Relevance
“…21 However, there are conflicting studies which do not clearly show age to be a prognostic factor for prostate cancer specific survival, particularly in patients with high Gleason grade. [21][22][23] In our study, in multivariate analysis of patients with GS 9-10 tumors, while the effect of age (P = 0.068) only trended toward significance, aspirin remained a highly statistically significant predictor of overall survival (P = 0.036). Thus, while our sample size precludes definite conclusions, it is unlikely that age was responsible for the highly statistically significant survival advantage in patients with GS 9-10 who took aspirin.…”
mentioning
confidence: 44%
“…21 However, there are conflicting studies which do not clearly show age to be a prognostic factor for prostate cancer specific survival, particularly in patients with high Gleason grade. [21][22][23] In our study, in multivariate analysis of patients with GS 9-10 tumors, while the effect of age (P = 0.068) only trended toward significance, aspirin remained a highly statistically significant predictor of overall survival (P = 0.036). Thus, while our sample size precludes definite conclusions, it is unlikely that age was responsible for the highly statistically significant survival advantage in patients with GS 9-10 who took aspirin.…”
mentioning
confidence: 44%
“…4,5 However, clinical findings to support this notion have to date been mixed. [6][7][8][9][10][11][12][13][14] Independent of the prognosis of early versus late-life onset PCa, it is possible that the biological pathways that drive this disease differ by age. However, to date, there have been no studies examining the similarities and differences in the prognostic drivers of PCa in different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Using the selection criteria just described, a total of 14 studies were identified for inclusion in this analysis (4,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). One of them was subsequently noted to be only partially analyzable because we were unable to determine the CSS (29).…”
Section: Resultsmentioning
confidence: 99%